Pendampingan Siswa Berkebutuhan Khusus dalam Pembelajaran Matematika pada Sekolah Inklusi di Kota Madiun - Nurulloh Olla Fransisca; Novitaria Arti Pujiastuti; Pupung Puspita Ningrum; Almira Dini Khairani; Edy Suprapto (Jurnal SOLMA, 2021)
Background: Inclusive education is an education where children with special needs can study in public schools in the environment around them. Therefore, good attention to students in inclusive schools is needed to support their learning success. Provide assistance to Students with Special Needs (SSN) in learning mathematics at inclusive schools in the city of Madiun. The partner in this service is SDN 2 Taman Kota Madiun, where the service activities are attended by all 4th grade students including SSN. The method of implementing the program includes the following stages: preparation, counseling, implementation, mentoring and evaluation. From the results of the implementation of the service, it gave several good impacts: 1) students become more motivated in math lessons, 2) Students more easily understand the fraction material presented with the help of learning media in the form of the Rainbow Fraction Tower prop that has been developed by the team. Based on the overall service activities that have been carried out, it can be concluded that learning mathematics with the help of media in the form of the Rainbow Fraction Tower props can have a very good influence on SSN, where they become more enthusiastic in learning and easy to understand fraction material.